CONNECTING WATERSCAPE GREAT MOSQUE OF WEST JAVA, GEDEBAGE, BANDUNG - Nur Maksum, Ahmad
The project is to design Great Mosque of West Java in Gedebage, Bandung. The purpose of this project is to build a provincial-level mosque as a worship and Islamic cultural center of West Java. That purpose is implemented into the functions of this mosque. Those are worship, education, social and economic functions. These functions will attract people to be closer to the mosque which will also prospering the mosque itself. The project is located in Bandung Teknopolis Region, which has a retention lake within it. This creates a strong environmental context for the project. This underlies the main concept of Great Mosque of West Java which is Connecting Waterscape. Connecting Waterscape is a concept that connects West Java society with water as a softscape, the local architecture value and the purification medium to make people closer to Allah swt. By the function and identity‘s approach of the building design, the main concept is realized by the building’s interaction with water as the softscape element, the local architectural identity and the element that creates spiritual ambience for the spaces. Thus, it can create a strong connection between the building with the environment and the building with people.